A case of severe neonatal transient hyperinsulinemic hypoglycaemia without identifiable risk factors: a case report - Asami Osada; Takeshi Arimitsu; Moe Kusakawa; Takane Kin; Mariko Hida (BMC, 2022)
Abstract Background Neonatal hypoglycaemia is one of the major metabolic disorders that causes irreversible brain injury. Assessing for maternal glucose metabolism disorders can predict and avoid this perinatal complication. Accordingly, diagnosing maternal gestational diabetes mellitus (GDM) is important in protecting neonatal neurological prognosis. However, there are various methods of screening for maternal GDM. The intervention for neonatal hypoglycaemia also varies within each guideline. Case presentation A female infant was born at 37 weeks of gestation by vaginal delivery with no asphyxia. Her mother had no abnormal findings, including glucose metabolism disorders, upon periodic prenatal visits. Upon routine examination at the first hour of life, the baby was lethargic, pale, hypotonic, and rarely cried. An emergent systemic evaluation was performed, and she was diagnosed with severe hyperinsulinemic hypoglycaemia with blood glucose of 11 mg/dL and insulin of 2.7 µU/mL. She was soon fed with milk and her symptoms of hypoglycaemia was resolved before receiving intravenous glucose infusion. Her blood glucose level reached 78 mg/dL 3 h after delivery. She was discharged home with her mother on day 6 of age without relapse of hypoglycaemia. Upon review, we determined that the mother was diagnosed with GDM during her previous pregnancy but not during this current pregnancy. The infant had no developmental delay upon check-up at 6 months. Conclusions The infant of this case was not a candidate for neonatal hypoglycaemia screening since her mother had no identifiable risk factors. This case suggests that previous maternal history of GDM might be the cause of neonatal hyperinsulinemic hypoglycaemia. Clinicians need to be aware of the possibility of hypoglycaemia among newborns with a maternal previous history of GDM, regardless of the mother's current diagnosis. Immediate oral feeding can be one of the treatments, even for symptomatic neonatal severe hypoglycaemia, when rapid intravenous access is difficult. The present case also suggests the necessity of considering neonatal outcomes as well as maternal ones when screening for maternal disorders of glucose metabolism.